Behavior of Major Statistical Estimators in Sampling Accounting Populations (Book). - Dominiak, Gere; Blocher, Edward (The Accounting Review, 1978)
Reviews the book "Behavior of Major Statistical Estimators in Sampling Accounting Populations," by John Neter and James K. Loebbecke.